2005
DOI: 10.1002/pola.20634
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of proton‐conducting copolyimides bearing pendant sulfonic acid groups

Abstract: A series of sulfonated copolyimides (co‐SPIs) bearing pendant sulfonic acid groups were synthesized from 1,4,5,8‐naphthalenetetracarboxylic dianhydride (NTDA), bis(3‐sulfopropoxy) benzidines (BSPBs), and common nonsulfonated diamines via statistical or sequenced polycondensation reactions. Membranes were prepared by casting their m‐cresol solutions. The co‐SPI membrane had a microphase‐separated structure composed of hydrophilic and hydrophobic domains, but the connecting behavior of hydrophilic domains was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 22 publications
2
78
0
Order By: Relevance
“…We also synthesized side-chain-type SPIs bearing pendant sulfoalkoxy groups, such as 2,2 0 -bis(3-sulfopropoxy)benzidine (2,2 0 -BSPB) and 3,3 0 -bis(3-sulfo-propoxy)benzidine (3,3 0 -BSPB), of which the chemical structures are also shown in Figure 1, and investigated the water stability of their membranes. [32][33][34] The data are also summarized in Table I. The side-chaintype SPIs based on 2,2 0 -BSPB and 3,3 0 -BSPB displayed much better water stability than the mainchain-type SPIs.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…We also synthesized side-chain-type SPIs bearing pendant sulfoalkoxy groups, such as 2,2 0 -bis(3-sulfopropoxy)benzidine (2,2 0 -BSPB) and 3,3 0 -bis(3-sulfo-propoxy)benzidine (3,3 0 -BSPB), of which the chemical structures are also shown in Figure 1, and investigated the water stability of their membranes. [32][33][34] The data are also summarized in Table I. The side-chaintype SPIs based on 2,2 0 -BSPB and 3,3 0 -BSPB displayed much better water stability than the mainchain-type SPIs.…”
mentioning
confidence: 82%
“…For NTDA-2,2 0 -BSPB/BAPB (2/1)-s (M7) and NTDA-2,2 0 -BSPB/BAPPS (2/1) (M8), of which the sulfur losses were smaller, no appreciable change in ' was observed in the whole range of RH even after the aging for 300 h. On the other hand, for NTDA-2,2 0 (or 3,3 0 )-BSPB/BAPB (2/1) (M6-1 and M9-1), of which the sulfur losses were larger, the larger decrease in ' took place at the lower RHs, as in the case of the aging at 130 C. Thus, the BSPB-based SPI membranes displayed rather poor proton conductivity stability especially with the aging at 130 C. With the aging at 100 C, some membranes showed reasonably high proton conductivity stability. The BSPB-based SPI membranes have the microphase-separated structure, 34 and rather small difference in membrane morphology might play a large role on their proton conductivity stability.…”
Section: Proton Conductivity Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Jannasch et al reported several side-group-acid poly-(ether sulfone)s with some attractive properties based on lithiation reaction. 24,31 Polyimides with side-group-acid substituents were also developed by Okamoto et al and Watanabe et al [32][33][34] To our knowledge, there are still no detailed reports related to the control of substitution sites through adjusting their various molecular structures. In addition, there are few reports of side-group-acid PEKs and their properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the scientific literature claiming to show good properties are only concerned with the PEM synthesis and basic membrane characterisation, while far less literature concerns work on membrane electrode assembly (MEA) and cell performance of hydrocarbon-based PEM materials [8].…”
Section: Introductionmentioning
confidence: 99%